The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s40169-016-0117-2
|View full text |Cite
|
Sign up to set email alerts
|

JNK inhibition reduces lung remodeling and pulmonary fibrotic systemic markers

Abstract: BackgroundLung remodeling and pulmonary fibrosis are serious, life‐threatening conditions resulting from diseases such as chronic severe asthma and idiopathic pulmonary fibrosis (IPF). Preclinical evidence suggests that JNK enzyme function is required for key steps in the pulmonary fibrotic process. However, a selective JNK inhibitor has not been investigated in translational models of lung fibrosis with clinically relevant biomarkers, or in IPF patients. MethodsThe JNK inhibitor CC‐930 was evaluated in the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 37 publications
1
44
2
2
Order By: Relevance
“…CC-930 is being tested in idiopathic pulmonary fibrosis and high-dose CC-930 caused elevation of hepatic transaminases when used for long-term treatment. (36) AS602801 is being tested in endometriosis and demonstrated favorable safety and tolerability after 5 months of administration. (37,38) Both diseases are benign, chronic inflammatory diseases, and the efficacy of the inhibitors has not been examined in malignant tumor patients; our results suggest that it is worth examining the safety and tolerability in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…CC-930 is being tested in idiopathic pulmonary fibrosis and high-dose CC-930 caused elevation of hepatic transaminases when used for long-term treatment. (36) AS602801 is being tested in endometriosis and demonstrated favorable safety and tolerability after 5 months of administration. (37,38) Both diseases are benign, chronic inflammatory diseases, and the efficacy of the inhibitors has not been examined in malignant tumor patients; our results suggest that it is worth examining the safety and tolerability in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…45 The JNK inhibitor CC-930 attenuated lung remodeling and collagen deposition and other pulmonary fibrotic systemic markers in house dust mite-induced fibrotic airway mouse model. 46 JNK1 and JNK2 KO mice were protected against hypercholesterolemia-induced endothelial dysfunction and atheroma formation. [47][48][49] The contribution of JNK2 signaling to muscle remodeling is increasingly appreciated.…”
Section: F I G U R E 1 1 Increased Expression Of Desmin and Vimentin mentioning
confidence: 91%
“…In particular, overexpression of miR-221 in normal rat kidney fibroblasts (NRK-49F cells) is able to prevent the angiotensin II-induced expression of fibronectin and alpha smooth muscle actin (αSMA) through targeting of ETS-1 [18]. Various reports have shown that the stress-activated protein kinase JNK1 is required for the development of fibrosis in multiple organs, including the liver [41,42], lung [43,44], kidney [45], and heart [46]. In particular, JNK1 is necessary for expression of profibrotic genes through stimulation of fibroblast activation, proliferation and transdifferentiation into myofibroblasts [45,[47][48][49].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Rapid dissociation of ribosomes in a miRNA-dependent manner represses elongation and prevents mRNA translation [41]. The current paradigm prevails that miRNAmRNA target interaction may lead to reductions in mRNA abundance due to an increase in mRNA degradation because of deadenylation, decapping, and exonucleolytic digestion of the mRNA [42,43]. In support of this model, many repressed mRNAs are deadenylated by miRNAs in vivo [42] and in vitro [40].…”
Section: Mirna-induced Posttranscriptional Repressionmentioning
confidence: 97%
See 1 more Smart Citation